THE EFFECT OF PROJECT-BASED LEARNING IN INCREASING STUDENT CREATIVITY AND INDEPENDENCE IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT DAIRI STATE VOCATIONAL SCHOOL - Romauli Nainggolan; Rizka Harfiani; Juli Maini Sitepu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to determine the influence of Project-Based Learning (PjBL) based learning in Islamic Religious Education (PAI) on the creativity and independence of MTs Negeri Dairi students. The type of research used was quasi-experimental with a pretest–posttest control group design involving 54 grade VIII students who were divided evenly into experimental and control classes. The experimental class uses the PjBL learning model, while the control class uses the conventional method. Creativity and independence were measured by a reliable questionnaire (α = 0.719; α = 0.717). The hypothesis test in this study is the MANOVA analysis, and the t-test. The results showed that PjBL-based learning had a significant effect (F = 126.22, p < 0.05, η² = 0.832). Individually, creativity (η² = 0.485) and independence (η² = 0.781) increased strongly. This study concludes that the use of the PjBL learning model has a significant influence on students' creativity and self-esteem in Islamic religious education learning.